STUDY OF USER’S RESPONSE ON THE PEDESTRIAN BRIDGE IN PEKANBARU CITY - Yulia Rahmawati; Yohannes Firza (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
A pedestrian bridge in urban areas exists not only to overcome crossing between people and vehicle but also gives a sense of security and comfort for its users. With a variety of user characteristics, the bridge has also used for other informal purposes. This phenomenon becomes interesting to study how the users respond to the various uses of the bridge. By using accidental sampling method for one hundred respondents, the field data has analysed in a simple linear regression model with data processing software. The result shows the safety, security, comfort, continuity and attractiveness are the primary considerations of users in utilizing the pedestrian bridge. Even though the physical condition has found less-expected, the user's response has generally categorized as sufficient.